Expression of EpCAM(MF) and EpCAM(MT) variants in human carcinomas - Fong, Dominic (BMJ Publishing Group, 2014)
AIMS: Regulated intramembrane proteolysis has been shown to be an important mechanism for oncogenic activation of epithelial cell adhesion molecule (EpCAM) through nuclear translocation of the intracellular domain EpICD. Recent studies have identified new membrane-bound EpCAM variants. To evaluate the prevalence of two membranous EpCAM variants in human tumours, we performed a large-scale expression analysis using specific antibodies against the extracellular domain EpEX (MOC-31 clone) and the intracellular domain EpICD (9-2 clone) of the EpCAM antigen by immunohistochemistry. MATERIAL AND METHODS: Two multi-tissue microarrays (TMA) series containing 1564 tissue samples each of 53 different histological tumour types were stained and compared. One TMA was stained for EpEX and one for EpICD. Membranous full-length EpCAM (EpCAM(MF)) expression in tissues was defined by the expression of EpEX and EpICD, while the truncated variant of EpCAM (EpCAM(MT)) was characterised by a significant loss of membranous EpICD expression compared with EpEX expression. RESULTS: We defined tumours with high EpCAM(MT) expression (ie, cancers of the endometrium and bladder), tumours with intermediate (ie, gastric, pancreatic, colorectal and oesophageal cancer) and tumours with low rates of expression of the EpCAM(MT) variant (ie, lung, ovarian, gallbladder, breast and prostate cancer). CONCLUSIONS: Our results indicate that loss of membranous EpICD expression is a common event in human epithelial carcinomas, arguing for the expression of different degrees of EpCAM(MF) and EpCAM(MT) variants across the most important tumour entities. Future studies evaluating the prognostic and predictive role of these variants in human malignancies, especially in patients treated with EpCAM-specific antibodies, are clearly warranted.